Forming bonds between molecules and communities through Project M - Murray, Claire A.; Holland, Laura; O'Brien, Rebecca; Parker, Julia E. (Frontiers in Communication, 2023)
Calcium carbonate is a compound that is well-recognized and very prevalent in daily life e.g., chalk, mussel shells and limescale. However, scientists still have many questions about its formation mechanisms, the different crystal forms it takes, and how we can control and direct this formation to produce this material with different properties. Project M was a chemistry citizen science project for UK secondary schools exploring the synthesis of samples of calcium carbonate under different reaction conditions and analyzing them at Beamline I11, an X-ray diffraction laboratory at the Diamond Light Source synchrotron. Science communication played a crucial role in the success of the project, connecting different communities to the science and creating unique opportunities to center and empower the Project M Scientists.